Smartphone addiction among adults: The role of smartphone use, fear of missing out (FoMO), and self-efficacy among Turkish adults - Gökçearslan, Şahin; Esiyok, Elif; Griffiths, Mark D.; Dogan, Murat; Turanci, Eda (Addicta: The Turkish Journal on Addictions, 2023)
Due to its computer-like features and applications, smartphone use has become a globally popular activity. Moreover, smartphones have become an important part of individuals’ daily lives. However, using smartphones excessively may result in smartphone addiction for a small minority of individuals. Consequently, the present study investigated the role of smartphone and social network site use, fear of missing out, and perceived self-efficacy in smartphone addiction among adults. In total, 488 adults (aged 20–65 years) participated in the study. The participants were recruited utilizing convenience sampling. Data were collected using an online questionnaire, and the relationship between the variables was tested using structural equation modeling. The results of the structural equation modeling showed that both smartphone use and fear of missing out positively affected smartphone addiction. The effect of social networking site use on smartphone use was significant. The findings of the present study found that fear of missing out and the time spent on smartphones explained 31% of the variance of smartphone addiction among adults, and smartphone usage predicted smartphone addiction. Based on the findings, excessive smartphone use and a higher level of fear of missing out appear to play a role in smartphone addiction. Social networking site use is also associated with an increase in the time spent on smartphones. Smartphone addiction prevention activities should focus on young adults. For future studies, psychological issues other than fear of missing out could be taken into consideration when examining the contributory factors of smartphone addiction.